Comparision of consumer oriented benefits of branded and branded generic diclofenac tablets - PRITI DHANDE,; VIVEK RATNAMRAJU,; SIMRAN CHAUHAN,; KALYANI KHADE, (International Journal of Pharma and Bio Sciences, 2019)
Branded (B) diclofenac sodium (Voveran) and some of its branded generic counterparts (B/G) (Reactin, Fenak and Difenac-F) were selected to scrutinize the information on drug packets, study the price structure, and evaluate their analgesic activity. Package information was studied and maximum percentage of weight variation of these tablets was calculated. Trade Margin (TM) and cost benefit to Pharmacist and patient was also calculated. Efficacy and onset of action for analgesic activity was studied in 5 groups of albino rats containing 6 rats each by tail flick model using an Analgesiometer. Tablets were crushed, made into suspension and given orally to the rats. Pain threshold was measured before administration (0 min) and then at 30 and 60 min after administration of the drugs. Data was analysed in Graph Pad Prism using ANOVA followed by Tukey’s test. Percentage weight variation was maximum for Tab. Fenak (4.1%) and least for Tab. Voveran (1.8%). Trade margin with Tab. Fenak was highest (407%) and least with Tab. Voveran (24%). Rise in pain threshold was maximum at 30 mins with Tab. Reactin (p<0.001) while significant rise in pain threshold was seen at 60 mins with Tab. Voveran (p<0.05) as compared to their baseline values. This rise was significant at both 30 and 60 min with Tab. Fenak (p<0.05) and Difenac-F (loosely-packed) (p<0.01). All the B/G versions of Diclofenac were found to be cheaper but at the same time effective analgesics as compared to their branded version